The Influence of Sharia Marketing and Religiosity on Transaction Decisions in Islamic Financial Institutions with Interest as a Mediation Variable - Astutiningsih, Sri Eka; Estiningrum, Sri Dwi; Aisah, Siti (Universitas Siliwangi, 2023)
Introduction to The Problem: Islamic financial institutions in Indonesia are growing rapidly. The development of Islamic financial institutions has attracted the attention of the public, both students and those who are already working.Purpose/Objective Study: This study aims to determine the influence of sharia marketing and religiosity on transaction decisions in Islamic financial institutions, with interest as a mediation variable.Design/Methodology/Approach: This research is a quantitative study and the sample in this study was 70 respondents. The data collection techniques using questionnaires with a Likert scale. The data analysis technique used is mediation analysis using the smart-PLS application.Findings: Based on the analysis test conducted, it shows that there is a direct influence between sharia marketing variables and interest variables; interest variables and religiosity variables affect transaction decision variables. The results of the religiosity variable test did not affect interest directly, and the sharia marketing variable did not affect the transaction decision variable directly. Based on the results of the mediation test, there is an indirect influence between sharia marketing variables on transaction decisions with interest as mediation variable. In contrast to the mediation results of the variable religiosity on transaction decisions with interest as a mediating variable, which show no indirect influence. The conclusion is there is full mediation where the interest variable is able to mediate sharia marketing variable on transaction decisions variable, and the interest variable cannot mediate the effect of religiosity on transaction decisions variable.